1058. In Vitro and In Vivo Antibacterial Activity of Cefiderocol against Burkholderia spp. (4th December 2021) - Oota, Merime; Hama, Hitomi; Yoshitomi, Toriko; Nakamura, Rio; Takemura, Miki; Yamano, Yoshinori; Hackel, Meredith; Sahm, Daniel F
Abstract: Background: Burkholderia spp. is an opportunistic pathogen associated with respiratory infections. Cefiderocol (CFDC), a siderophore cephalosporin approved in US and EU, is active in vitro against carbapenem-resistant Gram-negative bacteria including Burkholderia spp. This study examined in vitro and in vivo activity of CFDC against Burkholderia spp. Methods: MICs of CFDC and 13 marketed antibacterial drugs against 462 clinical isolates of Burkholderia spp. collected in 2014 - 2019 in 13 countries were determined by broth microdilution method according to CLSI guidelines. Only for CFDC, iron-depleted CAMHB was used. In a rat lung infection model, B. cepacia ATCC 25416 (CFDC MIC: ≤ 0.031 μg/mL, MEM MIC: 4 μg/mL) was used. Male CD (SD, immunocompetent, n=4-5) rats were infected by intrabronchial inoculation of the bacterial suspension including 1% nutrient agar. The humanized PK in plasma by administration of CFDC 2 g every 8 h (3-h infusion) and MEM 1 g every 8 h (0.5-h infusion) were recreated via the continuous intravenous infusion for 4 days, and the viable cfu in lungs were counted. Results: Against 462 strains, including 185 MEM non-susceptible isolates, CFDC showed MIC50 /MIC90 of ≤ 0.031/1 µg/mL, which was the lowest among the tested antibiotics. Among 185 MEM non-susceptible isolates, 94% of the isolates exhibited ≤ 4 µg/mL of CFDC MIC. In a rat lung infection model, CFDC and MEM showed bactericidal activity with 2.8 and 2.4 log10 CFU/lung decrease compared with non-treated control, respectively. By recreating the humanized PK exposure in this model, 100% and ca.35% of f T >MIC of CFDC and MEM in plasma has been achieved, respectively. The bactericidal activities of both compounds vs B. cepacia ATCC 25416 would be reasonable because the f T >MIC achieved in this model exceeds the target f T >MIC (75% for CFDC and 26% for MEM against Acinetobacter baumannii, respectively) required to cause 1 log10 reduction in murine thigh infection models 1, 2) . 1) M. Sabet. 2019. AAC 2) R. Nakamura. 2019. AAC In vitro activity of CFDC and comparator agents against Burkholderia spp. Conclusion: CFDC has potential for treating respiratory tract infections caused by Burkholderia spp. In critically ill patients, the recommended dosing regimen achieves 100% of f T >MIC of ≤ 4 ug/mL 3) .3) N. Kawaguchi. 2021. AAC Disclosures: Merime Oota, BSc, Shionogi TechnoAdvance Research & Co., Ltd. (Employee) Toriko Yoshitomi, -, Shionogi TechnoAdvance Research & Co., Ltd. (Employee) Rio Nakamura, BSc, Shionogi TechnoAdvance Research & Co., Ltd. (Employee) Miki Takemura, MS, SHIONOGI & CO., LTD. (Employee) Yoshinori Yamano, PhD, Shionogi (Employee) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)